X-ray Structural characterization of bioactive compounds from medicinalplants : Premna Obtusifolia and Cratoxylum Formosum ssp. Pruniflorum. - Ibrahim, Abdul Razak (Universiti Sains Malaysia, 2013)
Single crystal X-ray diffraction offers a complete approach to structural analysis. X-ray diffraction is the Only technique which provides the complete three dimensional structures of the chemical compounds. The formation of supramolecular arrangement in crystal structures is indeed important not just for the Construction of larger structures, this non-covalent bond assisted arrangement possess unique physical And chemical properties. In this research, the molecular and crystal structure of the medicinal plants Which are Premna obtusifojia (Verbenaceae) and Cratoxy/um formosum ssp. Pruniflorum are studied. Apart from this, other medicinally important compounds are also synthesized and their crystal structures Are also examined.